Thermal behaviour of cork and cork components - Şen, Ali; Van den Bulcke, Jan; Defoirdt, Nele; Van Acker, Joris; Pereira, Helena (Thermochimica Acta, 2014)
Thermal behaviour of cork and cork chemical components was studied with coupled differential scanning calorimetry-thermogravimetrical analysis (DSC-TGA) in order to gain insight into the role of the chemical components on the thermal degradation of cork. Cork samples of Turkey oak (Quercus cerris) and cork oak (Quercus suber) were chemically treated to selectively remove inorganic material, extractives and suberin, to allow characterization of klason lignin and methanolysis-depolymerized suberin. Since Q. cerris cork granulates contain phloemic impurities, phloem from Q. cerris bark was also subjected to the same treatments as cork. The thermal decomposition of both cork species is similar, starting above 200°C and increasing with increasing temperature until ashing at approximately 485°C. TGA curves of both corks are almost identical but a detailed view on the differential thermogravimetry (DTG) and DSC curves shows that the two materials differ from each other. Two exothermal devolatilization and char combustion reactions occur, peaking at approximately 313°C and 445°C. These peak temperatures shift to lower temperatures in suberin-free and extractive-free corks giving evidence of the heat retarding effect of suberin and extractives and possible catalytic effect of inorganics in desuberinised cork. Phloem thermal degradation is similar to that of cork although exothermal peak temperatures are higher. Phloem-containing Q. cerris cork granulates thus show clear potential for high temperature applications.
Keywords: Cork; DSC; Quercus cerris; Quercus suber; suberin; TGA

Lignin monomeric composition of corks from the barks of Betula pendula, Quercus suber and Quercus cerris determined by Py–GC–MS/FID - Marques, António Velez; Pereira, Helena (Journal of Analytical and Applied Pyrolysis, 2012)
Samples of cork tissues separated from the barks of Betula pendula, Quercus suber and Quercus cerris were characterized by Py–GC–MS/FID in respect to composition of lignin. The pyrolysis temperature influenced the yield of pyrolysis products, and in the conditions usually applied to wood pyrolysis (550 ◦C) suberin is only partially degraded into products. The lignin composition of the three corks showed predominantly a guaiacyl-based lignin: guaiacyl (G) units represented 85.7%, 96.4% and 93.7% of lignin respectively in B. pendula, Q. suber and Q. cerris corks, while syringyl (S) units amounted respectively to 11.9%, 2.5% and 2.7% and p-hydroxyphenyl (H) units to 2.4%, 1.1% and 3.6%. Pyrolysis of the woods of these same species confirmed the GS character of their lignins in contrast to the corks G-lignin type. The influence of ferulic acid in the results and its integration in a heterogeneous cork lignin structure was discussed.
Keywords: Betula pendula; Cork; Lignin composition; pyrolysis; Quercus cerris; Quercus suber

Study of thermochemical treatments of cork in the 150–400°C range using colour analysis and FTIR spectroscopy - Şen, Ali; Marques, António Velez; Gominho, Jorge; Pereira, Helena (Industrial Crops and Products, 2012)
A study of chemical transformations of cork during heat treatments was made using colour variation and FTIR analysis. The cork enriched fractions from Quercus cerris bark were subjected to isothermal heating in the temperature range 150–400 ◦ C and treatment time from 5 to 90min. Mass loss ranged from 3% (90min at 150 ◦ C) to 71% (60min at 350 ◦ C). FTIR showed that hemicelluloses were thermally degraded ﬁrst while suberin remained as the most heat resistant component. The change of CIE-Lab parameters was rapid for low intensity treatments where no signiﬁcant mass loss occurred (at 150 ◦ C L* decreased from the initial 51.5 to 37.3 after 20min). The decrease in all colour parameters continued with temperature until they remained substantially constant with over 40% mass loss. Modelling of the thermally induced mass loss could be made using colour analysis. This is applicable to monitoring the production of heat expanded insulation agglomerates.
Keywords: Colour analysis; Cork; FTIR; Heat treatment; Quercus cerris

Temperature-induced structural and chemical changes in cork from Quercus cerris - Şen, Ali; Miranda, Isabel; Pereira, Helena (Industrial Crops and Products, 2012)
The effects of temperature on anatomical and chemical characteristics of Quercus cerris cork were examined. Cork samples were subjected to isothermal air heating between 150 ◦ C and 400 ◦ C and analyzed for mass loss, cellular structure and chemical composition. The thermal decomposition of Q. cerris cork is similar to that of Q. suber cork. Cork is thermally stable below 200 ◦ C and after that degradation depended on temperature and heating time with increasing mass loss, i.e. 3% at 200 ◦ C 10min and 46% at 350 ◦ C 60min.With temperature and starting at 200 ◦ C, cells expanded, cell wall thickness was reduced and corrugations were lost. Extractives degraded at lower temperatures, although aliphatic extractives were found to be more stable. Suberin from Q. cerris was more heat resistant than Q. suber suberin, while lignin showed similar resistance. These results provide a basis for studies on the production of Q. cerris bark expanded cork agglomerates for insulation purposes.
Keywords: Cellular structure; Cork; Quercus cerris; suberin; Temperature

The cellular structure of cork from Quercus cerris var. cerris bark in a materials’ perspective - Şen, Ali; Quilhó, Teresa; Pereira, Helena (Industrial Crops and Products, 2011)
Cork in the outer bark of trees is among the valuable raw materials of biological origin due to properties that result mainly from its cellular structure. Large scale commercial utilization of cork has been only achieved with cork from Quercus suber. Another oak species, Quercus cerris, also contains substantial, albeit not continuous, regions of cork that are clearly visible to the naked eye but are so far considered as a waste material. Bark samples of Q. cerris var. cerris trees were collected from the Andırın province, Turkey. Cork portions were separated and their cellular structure was investigated with optical and electron scanning microscopy observations. The results were compared with Q. suber cork. Q. cerris cork has the typical features of cork tissues with a regular and radially aligned structure of suberized cells without intercellular voids, showing a ring structure and a distinction of earlycork and latecork cells. Solid volume fraction was estimated at 25% (22% in earlycork, 36% in latecork). In Q. cerris cork cells are smaller, cell wall thickness and solid volume fraction are higher, and the tissue is less homogeneous with a higher content of ligniﬁed inclusions than in Q. suber cork. These factors will negatively inﬂuence quality in regard to density and mechanical properties associated to elasticity. However, this does not impair its use for production of granulates and agglomerates, e.g. for insulation and energy absorption. Separation of the cork fraction from the bark is a step required before further processing and use.
Keywords: Bark; Cellular structure; Cork; Quercus cerris; Quercus suber

Estimation of Mediterranean forest transpiration and photosynthesis through the use of an ecosystem simulation model driven by remotely sensed data - Anselmi, Silvia; Chiesi, Marta; Giannini, Monica; Manes, Fausto; Maselli, Fabio (Global Ecology and Biogeography, 2004)
Aim This paper investigates the use of an ecosystem simulation model, FOREST-BGC, to estimate the main ecophysiological processes (transpiration and photosynthesis) of Mediterranean coastal forest areas using remotely sensed data. Location Model testing was carried out at two protected forest sites in central Italy, one of which was covered by Turkey oak (Circeo National Park) and the other by holm-oak (Castelporziano Estate). Methods At both sites, transpiration and photosynthesis measurements were collected in the field during the growing seasons over a four-year period (1999 and 2001 for the Turkey oak; 1997, 1999 and 2000 for the holm-oak). Calibration of the model was obtained through combining information derived from ground measurements and remotely sensed data. In particular, remote sensing estimates of the Leaf Area Index derived from 1 × 1-km NOAA AVHRR Normalized Difference Vegetation Index data were used to improve the adaptation of the model to local forest conditions. Results The results indicated different strategies regarding water use efficiency, ‘water spending’ for Turkey oak and ‘water saving’ for holm-oak. The water use efficiency for the holm-oak was consistently higher than that for the Turkey oak and the relationship between VPD and WUE for the holm-oak showed a higher coefficient of determination (R2 = 0.9238). Comparisons made between the field measurements of transpiration and photosynthesis and the model estimates showed that the integration procedure used for the deciduous oak forest was effective, but that there is a need for further studies regarding the sclerophyllous evergreen forest. In particular, for Turkey oak the simulations of transpiration yielded very good results, with errors lower than 0.3 mm H2O/day, while the simulation accuracy for photosynthesis was lower. In the case of holm-oak, transpiration was markedly overestimated for all days considered, while the simulations of photosynthesis were very accurate. Main conclusions Overall, the approach offers interesting operational possibilities for the monitoring of Mediterranean forest ecosystems, particularly in view of the availability of new satellite sensors with a higher spatial and temporal resolution, which have been launched in recent years.
Keywords: AVHRR; Ecosystem; FOREST-BGC; Mediterranean area; Modelling; photosynthesis; Quercus cerris; Quercus ilex; Transpiration; water efficiency

Estimation of Mediterranean forest transpiration and photosynthesis through the use of an ecosystem simulation model driven by remotely sensed data - Anselmi, Silvia; Chiesi, Marta; Giannini, Monica; Manes, Fausto; Maselli, Fabio (Global Ecology and Biogeography, 2004)
Aim This paper investigates the use of an ecosystem simulation model, FOREST-BGC, to estimate the main ecophysiological processes (transpiration and photosynthesis) of Mediterranean coastal forest areas using remotely sensed data. Location Model testing was carried out at two protected forest sites in central Italy, one of which was covered by Turkey oak (Circeo National Park) and the other by holm-oak (Castelporziano Estate). Methods At both sites, transpiration and photosynthesis measurements were collected in the field during the growing seasons over a four-year period (1999 and 2001 for the Turkey oak; 1997, 1999 and 2000 for the holm-oak). Calibration of the model was obtained through combining information derived from ground measurements and remotely sensed data. In particular, remote sensing estimates of the Leaf Area Index derived from 1 × 1-km NOAA AVHRR Normalized Difference Vegetation Index data were used to improve the adaptation of the model to local forest conditions. Results The results indicated different strategies regarding water use efficiency, ‘water spending’ for Turkey oak and ‘water saving’ for holm-oak. The water use efficiency for the holm-oak was consistently higher than that for the Turkey oak and the relationship between VPD and WUE for the holm-oak showed a higher coefficient of determination (R2 = 0.9238). Comparisons made between the field measurements of transpiration and photosynthesis and the model estimates showed that the integration procedure used for the deciduous oak forest was effective, but that there is a need for further studies regarding the sclerophyllous evergreen forest. In particular, for Turkey oak the simulations of transpiration yielded very good results, with errors lower than 0.3 mm H2O/day, while the simulation accuracy for photosynthesis was lower. In the case of holm-oak, transpiration was markedly overestimated for all days considered, while the simulations of photosynthesis were very accurate. Main conclusions Overall, the approach offers interesting operational possibilities for the monitoring of Mediterranean forest ecosystems, particularly in view of the availability of new satellite sensors with a higher spatial and temporal resolution, which have been launched in recent years.
The following values have no corresponding Zotero field: publisher: Blackwell Science Ltd
Keywords: AVHRR; Ecosystem; FOREST-BGC; Mediterranean area; Modelling; photosynthesis; Quercus cerris; Quercus ilex; Transpiration; water efficiency

Identification, measurement and interpretation of tree rings in woody species from mediterranean climates. - Cherubini, Paolo; Gartner, Barbara L; Tognetti, Roberto; Bräker, Otto U; Schoch, Werner; Innes, John L (Biological reviews of the Cambridge Philosophical Society, 2003)
We review the literature dealing with mediterranean climate, vegetation, phenology and ecophysiology relevant to the understanding of tree-ring formation in mediterranean regions. Tree rings have been used extensively in temperate regions to reconstruct responses of forests to past environmental changes. In mediterranean regions, studies of tree rings are scarce, despite their potential for understanding and predicting the effects of global change on important ecological processes such as desertification. In mediterranean regions, due to the great spatio-temporal variability of mediterranean environmental conditions, tree rings are sometimes not formed. Often, clear seasonality is lacking, and vegetation activity is not always associated with regular dormancy periods. We present examples of tree-ring morphology of five species (Arbutus unedo, Fraxinus ornus, Quercus cerris, Q. ilex, Q. pubescens) sampled in Tuscany, Italy, focusing on the difficulties we encountered during the dating. We present an interpretation of anomalies found in the wood structure and, more generally, of cambial activity in such environments. Furthermore, we propose a classification of tree-ring formation in mediterranean environments. Mediterranean tree rings can be dated and used for dendrochronological purposes, but great care should be taken in selecting sampling sites, species and sample trees.
Keywords: Arbutus unedo; Dendrochronology; Dendroecology; ecophysiology; Fraxinus ornus; Mediterranean climate; mediterranean tree rings; Mediterranean vegetation; Phenology; Quercus cerris; Quercus ilex; Quercus pubescens; wood anatomy

Identification, measurement and interpretation of tree rings in woody species from mediterranean climates. - Cherubini, Paolo; Gartner, Barbara L.; Tognetti, Roberto; Bräker, Otto U.; Schoch, Werner; INNES, JOHN L. (Biological reviews of the Cambridge Philosophical Society, 2003)
We review the literature dealing with mediterranean climate, vegetation, phenology and ecophysiology relevant to the understanding of tree-ring formation in mediterranean regions. Tree rings have been used extensively in temperate regions to reconstruct responses of forests to past environmental changes. In mediterranean regions, studies of tree rings are scarce, despite their potential for understanding and predicting the effects of global change on important ecological processes such as desertification. In mediterranean regions, due to the great spatio-temporal variability of mediterranean environmental conditions, tree rings are sometimes not formed. Often, clear seasonality is lacking, and vegetation activity is not always associated with regular dormancy periods. We present examples of tree-ring morphology of five species (Arbutus unedo, Fraxinus ornus, Quercus cerris, Q. ilex, Q. pubescens) sampled in Tuscany, Italy, focusing on the difficulties we encountered during the dating. We present an interpretation of anomalies found in the wood structure and, more generally, of cambial activity in such environments. Furthermore, we propose a classification of tree-ring formation in mediterranean environments. Mediterranean tree rings can be dated and used for dendrochronological purposes, but great care should be taken in selecting sampling sites, species and sample trees.
The following values have no corresponding Zotero field: accession-num: 12620063
Keywords: Arbutus unedo; Dendrochronology; Dendroecology; ecophysiology; Fraxinus ornus; Mediterranean climate; mediterranean tree rings; Mediterranean vegetation; Phenology; Quercus cerris; Quercus ilex; Quercus pubescens; wood anatomy

Leaf morphology and macronutrients in broadleaved trees in central Italy - Bussotti, Filippo; Borghini, Francesca; Celesti, Carlo; Leonzio, Claudio; Bruschi, Piero (Trees, 2000)
As part of an intensive monitoring programme (MON.I.TO, Intensive Monitoring of Forests in Tuscany), a 3-year survey was carried out, which included three tree species (beech, Fagus sylvatica L.; Turkey oak, Quercus cerris L.; holm-oak, Quercus ilex L.) located at six different sites. Leaves were sampled annually and analysed for nutrient concentrations (nitrogen, sulphur, phosphorus, magnesium, calcium, potassium and sodium) and morphological parameters (leaf area, dry weight, leaf mass per area, leaf thickness and leaf density). Results indicated considerable interannual variation of all the parameters. Differences between sampling sites indicated that, of all parameters measured, leaf mass per area could explain best the differences in field performance under conditions of stress. In fact, leaf mass per area was greater in the drier sites or when sea salt deposition occurred. Nevertheless, the variation of leaf mass per area over the 3 years did not reflect the differences in rainfall. Higher leaf mass per area was accompanied by lower concentrations of phosphorus and nitrogen, which could be a dilution effect due to an increase of structural carbon compounds in sclerophyllous leaves, as revealed by the total foliar content of these elements. Leaf mass per area as a measure of sclerophylly reached very high values among mesophile vegetation. Long-range transport of sea salt from coastal areas to mountain areas was mirrored in sodium concentrations of leaves.
Keywords: Fagus sylvatica; macronutrients; Quercus cerris; Quercus ilex; sclerophylly

Leaf morphology and macronutrients in broadleaved trees in central Italy - Bussotti, Filippo; Borghini, Francesca; Celesti, Carlo; Leonzio, Claudio; Bruschi, Piero (Trees, 2000)
As part of an intensive monitoring programme (MON.I.TO, Intensive Monitoring of Forests in Tuscany), a 3-year survey was carried out, which included three tree species (beech, Fagus sylvatica L.; Turkey oak, Quercus cerris L.; holm-oak, Quercus ilex L.) located at six different sites. Leaves were sampled annually and analysed for nutrient concentrations (nitrogen, sulphur, phosphorus, magnesium, calcium, potassium and sodium) and morphological parameters (leaf area, dry weight, leaf mass per area, leaf thickness and leaf density). Results indicated considerable interannual variation of all the parameters. Differences between sampling sites indicated that, of all parameters measured, leaf mass per area could explain best the differences in field performance under conditions of stress. In fact, leaf mass per area was greater in the drier sites or when sea salt deposition occurred. Nevertheless, the variation of leaf mass per area over the 3 years did not reflect the differences in rainfall. Higher leaf mass per area was accompanied by lower concentrations of phosphorus and nitrogen, which could be a dilution effect due to an increase of structural carbon compounds in sclerophyllous leaves, as revealed by the total foliar content of these elements. Leaf mass per area as a measure of sclerophylly reached very high values among mesophile vegetation. Long-range transport of sea salt from coastal areas to mountain areas was mirrored in sodium concentrations of leaves.
Keywords: Fagus sylvatica; macronutrients; Quercus cerris; Quercus ilex; sclerophylly

Screening of 18 Mediterranean plant species for volatile organic compound emissions - Owen, S; Boissard, C; Street, R A; Duckham, S C; Csiky, O; Hewitt, C N (Atmospheric Environment, 1997)
Eighteen tree and shrub species were screened for emissions of isoprene and other volatile organic compounds (VOCs) at three locations at Castelporziano (Italy) using a bag-enclosure sampling method followed by GC analysis. Thirty emitted compounds were identified. Temperature sensitivity of emissions of monoterpenes varied between species. Strong temperature dependencies were found for isoprene emissions. For monoterpene-emitting plant species with greatest ground cover in the dunes and macchia habitats, α-pinene, β-pinene and sabinene appeared to be the most frequently and abundantly emitted compounds. Isoprene was the major emission from the shrub species screened in the forest. Emissions from four dominant plant species were scaled up to estimate total fluxes from the dunes and macchia over a daytime period. Species with greatest biomass but low emission rates made a substantial contribution to total emissions.
Keywords: Arbutus unedo; Biogenic emissions; branch enclosure; Chrysanthemum praecox; cistus incanus; Cistus salvifolius; Cytisus sp.; Dittrichia sp.; Erica arborea; Erica multiflora; Helichrysum stoechas; isoprene; Juniperus oxycedrus; Juniperus phoenicea; Monoterpene; myrtus communis; Phillyrea angustifolia; Pinus pinea; Quercus cerris; Quercus ilex; Rubus fruticosus; Spartium junceum; VOCs